Narrative Review: Extraction and Characterization of Collagen from Various Fish Species - Mufidah, Aidatul; Rahayu, Wiranti Sri; Utami, Pri Iswati (Universitas Muhammadiyah Surakarta, 2024)
Collagen is a significant biomaterial in medical applications because of its unique properties, such as biodegradability and low antigenicity. As a result, collagen has been used in drug delivery systems and tissue engineering. Most commercial collagen is derived from cow skin, pig skin, or chicken waste. These terrestrial animal sources are inappropriate for many religious and ethnic groups, present regulatory and quality control challenges, and might contain contaminants and biological toxins, including BSE (mad cow disease). This review summarizes an overview of recent research conducted from 2014 to 2024 on collagen extraction from fish. Data were retrieved from online publications on the Pubmed database and covered fish collagen, extracts, and characterization. Fish by-products have been shown to be useful for producing collagen that can substitute porcine and bovine sources. Collagen extracted from fish body parts is classified as type 1. Some typical marine collagen characterization methods thats are often used are FTIR and SDSPAGE. Fish by-products have been proven to be valuable to produce collagen which can replace porcine and bovine sources. Fish by-products may be an alternative to the more prevalent collagen extraction methods.